Influence of Intercropping Patterns of Beet Leaf on Seed Yield, its Attributes and Economics of Onion Seed Crop - Saini, Karan Singh; Dhankhar, S. K.; Choudhary, Desh Raj; Singh, Davinder; Kumar, Vikash; Dalal, Pradeep Kumar (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during (October–June, 2018–19 and 2019–20) at CCS Haryana Agricultural University, Hisar in the Sub-tropical Northern plain of India with the aim to find a remunerative intercropping strategy for optimum onion seed production with green leaf cuttings of beet leaf. This investigation involved 17 intercropping arrangements as treatments, which exhibited cultivating multi-cut beet leaf crop with onion seed crop in different row arrangements (1 or 2 rows) and varied cutting frequency (3–6 cuttings) of beet leaf to understand its impact on onion seed yield and income generation. Onion seed crop (sole crop) recorded the highest benefit-cost ratio (3.37:1) with superior yield attributes namely, seed yield (581.2 kg ha-1), seed stalk length (104 cm), seed stalk diameters (2.7 cm), seed stalk bulb-1 (10.3), seed weight umbel-1 (2.5 g). Among the intercropping treatments, Onion+Beet leaf (1 row) with 3 cuttings, recorded the highest onion seed yield (487.5 kg ha-1) and benefit-cost ratio (2.76:1). In contrast, Onion seed crop+Beet leaf (2 rows) with 3 cuttings and left for beet leaf seed crop was performed poorly in all the parameters and recorded as the minimum value for seed yield (329.5 kg ha-1), seed stalk length (85.5 cm), flower stalk diameter (1.9 cm), seed stalk bulb-1 (6.7) and B:C ratio (1.71). Therefore, the intercropping strategy of Onion+Beet leaf (1 row) with 3 cuttings can potentially raise the vegetable growers’ income.